Quantum mechanical insights into Edge-Dependent electronic properties of phosphorene nanoribbons - Mohammadamir Bazrafshan; Adeleh Vatankhahan; Farhad Khoeini; Omid Farzadian (Results in Physics)
Phosphorene, known for its anisotropic physical properties, exhibits a direct moderate electronic band gap, making it a candidate for electronic applications. This study investigates the electronic properties of phosphorene nanoribbons (PNRs) with different edge configurations using density functional theory (DFT). It addresses the role of sublattices in zigzag and armchair phosphorene nanoribbons, identifying six different edge configurations for zigzag and two for armchair edges. The density of states (DOS) at the valence band maximum (VBM) can be strongly different on the sublayers in some zigzag edge configurations, which can be useful in many applications such as sensing. Conversely, the conduction band minimum (CBM) shows low sensitivity to the edge configuration, indicating that electron transport can be less affected than hole transport. The electronic band gap of both armchair and zigzag nanoribbons decreases with increasing width, which also varies with edge type. Armchair nanoribbons undergo compressive strain, while zigzag nanoribbons experience tensile stress compared to the corresponding directions in phosphorene. These findings provide insight into the design of phosphorene-based nanodevices, including transistors, sensors, and flexible electronics.